2014
DOI: 10.1111/tpj.12436
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis, elicitation and roles of monocot terpenoid phytoalexins

Abstract: SUMMARYA long-standing goal in plant research is to optimize the protective function of biochemical agents that impede pest and pathogen attack. Nearly 40 years ago, pathogen-inducible diterpenoid production was described in rice, and these compounds were shown to function as antimicrobial phytoalexins. Using rice and maize as examples, we discuss recent advances in the discovery, biosynthesis, elicitation and functional characterization of monocot terpenoid phytoalexins. The recent expansion of known terpenoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
231
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 250 publications
(239 citation statements)
references
References 196 publications
(345 reference statements)
8
231
0
Order By: Relevance
“…ZmAN2 was first described in a differential display analysis of highly elicited transcripts following F. graminearum challenge of maize silks (Harris et al, 2005). Following the first description of ZmAN2, pathogen-elicited transcripts have been observed and reported in a large number of maize studies with diverse microbes Schmelz et al, 2011Schmelz et al, , 2014van der Linde et al, 2011;Vaughan et al, 2014;Christie et al, 2017). The nearly ubiquitous presence of ZmAN2 as a pathogen defense transcript marker is consistent with the essential biosynthetic role in the modular formation of multiple specialized diterpenoid metabolites, including not only A-and B-series kauralexins but also dolabralexins.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ZmAN2 was first described in a differential display analysis of highly elicited transcripts following F. graminearum challenge of maize silks (Harris et al, 2005). Following the first description of ZmAN2, pathogen-elicited transcripts have been observed and reported in a large number of maize studies with diverse microbes Schmelz et al, 2011Schmelz et al, , 2014van der Linde et al, 2011;Vaughan et al, 2014;Christie et al, 2017). The nearly ubiquitous presence of ZmAN2 as a pathogen defense transcript marker is consistent with the essential biosynthetic role in the modular formation of multiple specialized diterpenoid metabolites, including not only A-and B-series kauralexins but also dolabralexins.…”
Section: Discussionmentioning
confidence: 99%
“…(+)] stereochemistry (Morrone et al, 2010). These three different combinations were selected, since ent-, syn-, and (+)-CPP represent the known stereochemical variations of class II diTPS products occurring naturally in many monocots (Peters, 2010;Schmelz et al, 2014). When coexpressed with ZmAN2, ZmKSL4 converted ent-CPP into a single product with an unusual fragmentation pattern showing major mass ions of mass-to-charge ratio (m/z) 204, 189, and 216, in addition to the mass ions m/z 257 and 272 that are characteristic of labdane diterpenoid structures (Fig.…”
Section: Zmksl4 Produces An Unusual Diterpene Scaffoldmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference between the activity exhibited by AtKO and OsKO2 may reflect their distinct evolutionary contexts. In particular, although Arabidopsis seems to be representative of the Brassicaceae plant family, which does not produce any more specialized LRDs, only GA, and contains just one CYP701 family member, rice is representative of the Poaceae plant family, where it has been indicated that more specialized LRDs arose early, with widespread retention (20), and rice contains a number of CYP701A subfamily members with distinct function (9)(10)(11). This presumably exerted differing selective pressures on these genes, which was examined by molecular phylogenetic analysis of all characterized members of the CYP701 family ( Fig.…”
Section: Resultsmentioning
confidence: 99%